2020
DOI: 10.1002/jclp.23042
|View full text |Cite
|
Sign up to set email alerts
|

Attrition and attendance in group therapy for university students: An examination of predictors across time

Abstract: Objectives There exists a dearth of research focused explicitly on predictors of attrition, particularly in the area of group therapy, where both attrition and attendance becomes of primary concern. The present study examined both pretreatment and treatment‐specific variables in the prospective prediction of attendance and attrition in group therapy. Method Fifty‐two participants were randomized to one of two 12‐week group treatments. Participants completed baseline interviews and questionnaires, as well as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Treatment adherence in this study was very strong; close to 90% of participating fathers completed all 13 sessions of the intervention and stayed in the study 1 year post-intervention. This adherence rate is 15-20% better than many reported retention rates (Gulamani, Uliaszek, Chugani, & Rashid, 2020;Michael, 2018). One possible reason for the strong retention rate may be the intervention's group format; studies have found fathers are more receptive to support groups than individual therapy sessions (Duhig, Phares, & Birkeland, 2002;Glynn & Dale, 2015), a factor social work practitioners may want to take into consideration.…”
Section: Discussionmentioning
confidence: 56%
“…Treatment adherence in this study was very strong; close to 90% of participating fathers completed all 13 sessions of the intervention and stayed in the study 1 year post-intervention. This adherence rate is 15-20% better than many reported retention rates (Gulamani, Uliaszek, Chugani, & Rashid, 2020;Michael, 2018). One possible reason for the strong retention rate may be the intervention's group format; studies have found fathers are more receptive to support groups than individual therapy sessions (Duhig, Phares, & Birkeland, 2002;Glynn & Dale, 2015), a factor social work practitioners may want to take into consideration.…”
Section: Discussionmentioning
confidence: 56%
“…This protocol review describes the implementation of social VR support groups for a rare disease population with substantial participation (72.8%, SD 25.7%) and retention rates (86.7%, SD 0.35%). These rates compare favorably to historical data describing outpatient mental health attrition rates ranging widely with a range of 25% to 75% in children and adolescents [34]. Prior to the launch of our VR-based approach, and despite expressing a desire to participate in support groups, our adolescent and young adult cancer social worker was unable to convince any significant number of patients to return to the hospital for in-person groups.…”
Section: Principal Findingsmentioning
confidence: 59%
“…The ratios of patients found to be psychologically vulnerable, and those interested and actually attending the psychological programme are comparable with the take-up of psychosocial services in the ART setting in previous studies ( Spoletini et al , 2022 ). The average session attendance rate (88.8%) was impressively high, and the attrition rate (5.5%) was low, as compared to that of psychological interventions in general, where the dropout is estimated to be 17% in efficacy studies and 26% in effectiveness studies ( Swift and Greenberg, 2012 ), and to attrition rates in group settings ranging between 25% and 31% ( Hofmann and Suvak, 2006 ; Gulamani et al , 2020 ). This points to the feasibility of the intervention, and to the remarkably high motivation of women facing infertility to raise in all possible ways their chances of having a child.…”
Section: Discussionmentioning
confidence: 98%